Bus ticket reservation system / Tan Chin Kuang - Tan, Chin Kuang (2002)
Electronic Commerce is one of the most important aspects of the Internet to emerge. It allows people to exchange goods and services immediately and with no barriers of time or distance. Any time of the day or night, people can go on line and buy almost anything they want. Puduraya Bus Ticket Agent (PBTA) System is an application based on the e-commerce technology. Its makes use of client/server architecture to provide people with on line access to bus companies' databases. The main purpose of PBTA is to offer more convenient way for people to get the ticket of bus companies that located in Puduraya. There are 2 major modules in this application, which are user and administrator. User module enables people to acquire information and make a reservation of bus ticket. Administrator module provides extra facilities for the administrator to carry out housekeeping tasks and to maintain the database online. It is strongly believed that emerging of PBTA System would make people life more comfortable and easier, as well as improving services of bus companies.